(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study will introduce the readers to the background of the brand and the level of customer perception towards Bigbrew’s brand quality: the basis for formulating a marketing development strategy plan to increase profitability and achieve higher sales volume from new products. Related Literature and Studies, theoretical framework, conceptual framework, statement of the problem, the hypothesis, the significance of the study, and the definition of terms. The study presents data on the Perception of customers towards the Brand quality of BigBrew, problems encountered by the respondents in terms of customer perception and brand quality, and the statistical tools used were frequency, percentage, weighted mean, and Pearson and Likert scale. Based on the data from the majority of the respondents, based on the results, the design of the product can catch the customer’s attention. The majority of the respondents were from Barangay Bahay Toro, Project 8 Quezon City. The indicator that got the highest weighted mean in terms of brand positioning is “The design of the product can catch the customer’s attention”; in terms of customer support quality is “They answer the concern about the product,” in terms of Price is “ The price of the product is affordable,” in terms of Product quality is “ The product is worth the money,” in terms of Online reviews is “ The Bigbrew deserves a 5-star rating” in terms of Brand image is “ Bigbrew has a good image among the customer” in terms of Brand recall is “ The customer can quickly recall the shop based on the logo” in terms of Brand recognition is “ The customer prefers Bigbrew’s among its competing brands” in terms of Brand Association is “The product of Bigbrew is well-priced.”, The customer becomes interested in buying a product in Bigbrew because of their friend/s.” in terms of Brand awareness is “ When you are in the mood for a milk tea, the Bigbrew is the first to come to mind.”